Evaluating complete Streets. The value of designing roads for diverse modes, users and activities. - Litman, Todd (My University, 2013)
Complete streets refers to roads designed to accommodate diverse modes, users and activities including walking, cycling, public transit, automobile, nearby businesses and residents. Such street design helps create more multi-modal transport systems and more livable communities. This report discusses reasons to implement complete streets and how it relates to other planning innovations. Complete streets can provide many direct and indirect benefits including improved accessibility for non-drivers, user savings and affordability, energy conservation and emission reductions, improved community livability, improved public fitness and health, and support for strategic development objectives such as urban redevelopment and reduced sprawl. Net benefits depend on the latent demand for alternative modes and more compact development, and the degree that complete street projects integrate with other planning reforms such as smart growth, New Urbanism and transportation demand management.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsplanung; Straßenbau; Radverkehrsanlage; Fahrradstreifen